Occupational health and health care in Russia and Russian Arctic: 1980–2010 - Dudarev, Alexy A.; Odland, Jon Øyvind (International Journal of Circumpolar Health, 2013)
Background. There is a paradox in Russia and its Arctic regions which reports extremely low rates of occupational diseases (ODs), far below those of other socially and economically advanced circumpolar countries. Yet, there is widespread disregard for occupational health regulations and neglect of basic occupational health services across many industrial enterprises. Study design and methods. This review article presents official statistics and summarises the results of a search of peer-reviewed scientific literature published in Russia on ODs and occupational health care in Russia and the Russian Arctic, within the period 1980 2010. Results. Worsening of the economic situation, layoff of workers, threat of unemployment and increased work load happened during the ‘‘wild market’’ industrial restructuring in 1990 2000, when the health and safety of workers were of little concern. Russian employers are not legally held accountable for neglecting safety rules and for underreporting of ODs. Almost 80% of all Russian industrial enterprises are considered dangerous or hazardous for health. Hygienic control of working conditions was minimised or excluded in the majority of enterprises, and the health status of workers remains largely unknown. There is direct evidence of general degradation of the occupational health care system in Russia. The real levels of ODs in Russia are estimated to be at least 10 100 times higher than reported by official statistics. The low official rates are the result of deliberate hiding of ODs, lack of coverage of working personnel by properly conducted medical examinations, incompetent management and the poor quality of staff, facilities and equipment. Conclusions. Reform of the Russian occupational health care system is urgently needed, including the passing of strong occupational health legislation and their enforcement, the maintenance of credible health monitoring and effective health services for workers, improved training of occupational health personnel, protection of ...